Emotional Color Palette of Visually Impaired Individuals Through Sense of Touch in Daily Wear Garments - Sharma, Deepshikha; Carla Cristina da Costa Pereira (Convergences - Journal of Research and Arts Education, 2025)
The sense of touch elicits various flows of thoughts and feelings unique to everyone specifically for visually impaired individuals. It shows in different research that different emotions arise in response to touching various textures. This research paper attempts to delve into the diverse emotional experiences of visually impaired individuals when they interact with different-coloured fabrics through tactile sensation. Despite their visual impairment, these individuals possess a keen sensory ability to discern textures of different types of fabrics in daily wear garments. This research is using user experience methodology and questionnaire method (5-point Likert scale tool) for the collection of the data. The primary focus lies on elucidating the emotional impact of design on the daily lives of visually impaired individuals. The author selects fabrics, including a 100% Viscose T-shirt in white and black, 100% polyester T shirt in brown and green, 100% cotton T-shirt in yellow and blue and 100% Linen casual wear shirt in white and each fabric category maintains consistent quality. The Plutchik Wheel of Emotions is using in this research to select emotions, specifically focusing on the 8 basic emotions. Memory, cultural associations, and individual preferences also significantly influence the emotional experiences in tactile fabric perception. The results indicate that the 100% linen casual wear shirt in white and black evokes the same loathing emotion, while the 100% cotton T-shirt in yellow elicits ecstasy, with blue prompting admiration. The 100% polyester T shirt in brown and green also induces ecstasy but the level of ecstasy is more in green. Additionally, the 100% viscose T-shirt in black and white triggers ecstasy, with the highest intensity observed in the white T-shirt. These findings give the emphasize and connection between tactile sensation, fabric properties, and emotional responses in visually impaired individuals.